Sustainable functional finishing for cotton fabrics using screen-printing process and gallotannin - Kyung Hwa Hong (SpringerOpen, 2021)
Abstract To seek a more environmentally friendly textile finishing technique, the screen-printing method was adopted to apply functional material to cotton fabrics. In addition, gallotannin was used as a functional material because it is naturally abundant in many plant-derived substances and shows various health-promoting features such as antimicrobial, antioxidant, and other attractive properties. Therefore, a gallotannin/thickener paste was applied to the surface of cotton fabrics through the screen-printing technique, and the gallotannin-printed cotton fabrics were thoroughly investigated using scanning electron microscope (SEM), Fourier-transform infrared spectroscopy (FTIR), and other methods. The gallotannin printed area was substantially brown in appearance, and gallotannin moiety appeared to combine with cotton cellulose through heat treatment. Furthermore, functional properties of the gallotannin-printed cotton fabrics were examined in terms of antibacterial activity, deodorizing property, and ultraviolet-blocking property, of which it demonstrated excellent abilities. However, the antibacterial ability toward Gram-negative bacteria (K. pneumoniae) decreased as the laundry cycle increased.